Country Partnership Framework for the Republic of Liberia for the Period FY19 - FY24 - World Bank Group (World Bank, Washington, DC, 2018)
The Liberian economy is undergoing a process of structural transformation, as the dominanceof agriculture and mining gradually gives way to a rising services sector. Much of the Liberian economy is structured around foreign direct investment (FDI) and the development of private agricultural, mining, and forestry concessions. The Liberian economy showed signs of recovery in 2017-2018, amid significant fiscal and external imbalances. The medium-term outlook remains positive, assuming the new government maintains prudent macroeconomic policies, pursues a judicious borrowing policy, and implements planned structural reforms. The favorable medium-term growth outlook also assumes that sound macroeconomic management and structural reforms will strengthen investor confidence. The Government’s medium-term development strategy (July 2018-June 2023), the Pro-poor Agenda for Prosperity and Development (PAPD), is designed around the priorities set forth in President Weah’s inaugural speech and State of the Nation address: (i) combatting corruption; (ii) improving efficiency and accountability in the public sector; (iii) promoting honesty and transparency in the private sector; (iv) narrowing infrastructure gaps, especially in the southeast; and (v) creating jobs, especially for young workers. The Country Partnership Framework emphasizes the importance of shifting the focus of the WBG program from being infrastructure intensive under the previous CPS toward a more balanced approach with greater attention to education, agriculture, economic empowerment of women and youth, and maternal and child health. WBG will support smallholder commercialization and private-sector investment in agribusiness by fostering productive business linkages among smallholder farmers, selected agribusiness firms, and business-development services—with a special focus on constraints faced by women and youth.